2018
DOI: 10.3329/bjp.v13i3.36716
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of endophytic fungi isolated from six Sri Lankan plants of the family Cyperaceae

Abstract: <p class="Abstract">In a study designed to determine the antibacterial potential of endophytic fungi inhabiting plants of Cyperaceae family, 72 morphologically distinct endophytic fungi were isolated from six plants and their antibacterial activities against two Gram positive and three Gram negative pathogenic bacterial species were examined. Two antibacterial metabolites from two endophytes were also isolated and their chemical structures and minimum inhibitory concentrations were determined. Sixty six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
(37 reference statements)
2
11
1
Order By: Relevance
“…Seventeen endophytic fungi, twelve from aerial parts and five from roots, were isolated from C. iria plants. A previous study using the Cyperaceae plants C. brevifolius , C. melanospermus , C. alternifolius , C. bulbosus , C. rotundus and F. miliaceae reported that these plants are good reservoirs for endophytic fungi with a high species richness with no obvious preference for endophyte location in the plants, aerial or roots . In the current study, C. iria provided a similar number of fungi to C. melanospermus from the above‐mentioned report .…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Seventeen endophytic fungi, twelve from aerial parts and five from roots, were isolated from C. iria plants. A previous study using the Cyperaceae plants C. brevifolius , C. melanospermus , C. alternifolius , C. bulbosus , C. rotundus and F. miliaceae reported that these plants are good reservoirs for endophytic fungi with a high species richness with no obvious preference for endophyte location in the plants, aerial or roots . In the current study, C. iria provided a similar number of fungi to C. melanospermus from the above‐mentioned report .…”
Section: Resultssupporting
confidence: 70%
“…A previous study using the Cyperaceae plants C. brevifolius , C. melanospermus , C. alternifolius , C. bulbosus , C. rotundus and F. miliaceae reported that these plants are good reservoirs for endophytic fungi with a high species richness with no obvious preference for endophyte location in the plants, aerial or roots . In the current study, C. iria provided a similar number of fungi to C. melanospermus from the above‐mentioned report . The endophytic fungi isolated and antifeedant activities obtained from the no choice leaf disc assay are shown in Table .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations